Juridical Review Of The Land Dispute Over Right To Build Between Pundenrejo Farmers And PT. Indah Perdana (Study In Pati Regency) - Maghfirotul Aulia (Faculty of Law, Universitas Negeri Semarang, 2025)
In the context of an agrarian country like Indonesia, land not only has strong economic value, but also social and cultural value, especially for rural communities who depend on the agricultural sector for their livelihoods. This is the case in Pundenrejo Village, Pati Regency, where there is a dispute between local farmers and PT LPI, which has an HGB on land that is also claimed as cultivated land by residents. The land dispute between Pundenrejo farmers and PT Laju Perdana Indah (PT LPI) in Pati Regency reflects the complexity of agrarian problems in Indonesia, especially related to the issuance of Right To Build (HGB) on land that is still the object of community claims. This research aims to examine juridically the process of issuing HGB to PT LPI as well as legal protection for people who have claims of inheritance Right to the land. The research method used is normative juridical with a document study approach and relevant legislation. The results show that the issuance of HGB to PT LPI has not fully fulfilled the principle of “clean and clear” as stipulated in UUPA No 5 of 1960. Therefore, it is necessary to improve the HGB issuance mechanism through land ownership audits, public consultation, and participatory dispute resolution to realize legal certainty and justice for all parties.